In-process real-time probiotic phenotypic strain identity tracking: The use of Fourier transform infrared spectroscopy - Deidda, Francesca; Cordovana, Miriam; Bozzi Cionci, Nicole; Graziano, Teresa; Di Gioia, Diana; Pane, Marco (Frontiers in Microbiology, 2022)
Probiotic bacteria, capable of conferring benefits to the host, can present challenges in design, development, scale-up, manufacturing, commercialization, and life cycle management. Strain identification is one of the main quality parameters; nevertheless, this task can be challenging since established methodologies can lack resolution at the strain level for some microorganisms and\or are labor and time consuming. Fourier Transform Infrared spectroscopy (FTIRS) has been largely used for the investigation of pathogenic species in the clinical field, whereas only recently has been proposed for the identification of probiotic strains. Within the probiotic industrial production, bacterial strain can be subjected to stressful conditions that may affect genomic and phenotypic characteristics, therefore a real time monitoring of all the sequential growth steps is requested. Considering the fast, low-cost and high-throughput features, FTIRS is an innovative and functional technology for typing probiotic strains from bench top experiments to a large-scale industrial production, allowing the monitoring of stability and identity of probiotic strains. In this study, the discriminatory power of FTIRS was assessed for 4 Lactiplantibacillus plantarum probiotic strains using different growth conditions, including temperature, 30 °C and 37 °C, and medium, broth and agar, after consecutive sub-culturing steps. A comparison between the generated spectra with PGFE profiles was also performed. FTIRS was able not only to distinguish the strains of L. plantarum at different growth conditions, but also to prove the phenotypic stability of L. plantarum type strain LP-CT after 6 growing steps. Regardless the growth conditions, FTIRS spectra related to LP-CT constituted a unique hierarchical cluster, separated from the other L. plantarum strains. These results were confirmed by a PFGE analysis. In addition, based on FTIRS data, broth cultures demonstrated a higher reproducibility and discriminatory power with respect to agar ones. These results support the introduction of FTIRS in the probiotic industry, allowing a step-by-step monitoring of massive microbial production and guaranteeing the stability and the purity of the probiotic strain. The proposed novel approach can constitute an impressive improvement in the probiotic manufacturing process.